Aesthetics - Vola, Joonas (Palgrave Macmillan, 2022)
Aesthetics is the study of the sensible in the sensuous. In judging sensitivity and sense-making, aesthetics becomes a subject of ethical and political debate. The Arctic is traditionally aestheticized as a uniformly frozen and wild clime, with its people depicted from the Western perspective as exotic Others and subjected to certain colonial and commercial practices. To achieve a contemporary image of the politics of Arctic aesthetics, the chapter undertakes a case study of the video artwork Grind (2011) by Jenni Hiltunen, criticized as an instance of cultural appropriation of the indigenous Sámi people. The analysis extends the Arctic beyond its geographically defined borders into a realm marked by Othering, marginality, appropriation, colonialism and a particular political economy.